Chief sustainability officers at work : how CSO's build successful sustainability and ESG strategies - Pagitsas, Chrissa (Apress, 2022)
Read over 20 exclusive, in-depth interviews with chief sustainability officers (CSOs) of Fortune 500 companies such as Amazon, Coca-Cola, and Procter & Gamble and globally recognized brands such as IKEA and Netflix. These CSOs reveal how they deliver positive environmental and social impact through their companies' core products and services and generate revenue growth while tackling unique leadership, change management, regulatory and stakeholder challenges.